The best of the best : fifty years of communications and networking research - Tranter, William H.; Institute of Electrical and Electronics Engineers (New York : John Wiley & Sons, 2007)
The book divides these 50 papers into two major categories (Communications and Networking) and groups them by decade
Includes bibliographical references
Keywords: Computer networks -- Research; Data transmission systems -- Research; Wireless communication systems -- Research